Studies on liquid sheet disintegration in airblast atomizers - Rizk, N. K. (Cranfield University, 1976)
The work in this thesis has been devoted to studying the influence of liquid film thickness on the characteristics of airblast atomizers. The research was carried out using two special atomizers that were both designed to produce flat liquid sheets which were atomized by high velocity air streams acting on both sides of the shoot. The liquid was injected through sintered plates in the first design, while the film issued from a variable gap, slot in the second design.